Treatments and regulatory mechanisms of acoustic stimuli on mood disorders and neurological diseases - Chen, Yikai; Sun, Julianne; Tao, Junxian; Sun, Tao (Frontiers in Neuroscience, 2024)
Acoustic stimuli such as music or ambient noise can significantly affect physiological and psychological health in humans. We here summarize positive effects of music therapy in premature infant distress regulation, performance enhancement, sleep quality control, and treatment of mental disorders. Specifically, music therapy exhibits promising effects on treatment of neurological disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). We also highlight regulatory mechanisms by which auditory intervention affects an organism, encompassing modulation of immune responses, gene expression, neurotransmitter regulation and neural circuitry. As a safe, cost-effective and non-invasive intervention, music therapy offers substantial potential in treating a variety of neurological conditions.